A novel incremental sheet metal forming process for long and open section profiles. Issue 1 (1st May 2022) - Essa, A; Abeyrathna, B; Rolfe, B; Weiss, M
Abstract: Complex components from High Strength Steel (HSS) can be formed with Flexible Roll Forming (FRF). However, flange wrinkling limits the part shape complexity that can be achieved and hence limits its application in the automotive industry. A novel forming technology is introduced in this study, Incremental Shape Rolling (ISR), where a pre-cut blank is clamped between a top and bottom die and then a single forming tool incrementally forms the material according to the bottom die's geometry. It is believed that ISR can significantly reduce the wrinkling issue compared to FRF. In the contrast to the incremental sheet forming process, ISR allows the manufacture of long and open sections from HSS sheets. In this work, the experimental prototyping trials of the ISR process are performed using a 5-axis milling machine and then are used to validate the FEA model which is developed to simulate and analyse the deformation behaviour of the ISR process. The results show a clear development of transverse tensile strain along the flange which can overcome the wrinkling issue when the ISR process is applied to complex profiles.